Textbook of cancer epidemiology - Adami, Hans-Olov.; Hunter, David J. (David John); Trichopoulos, Dimitrios (New York ; Oxford : Oxford University Press, 2008)
This title gives a systematic account of what is currently known about the epidemiology and the potential of primary prevention for most forms of human cancer.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cancer -- Epidemiology